Eksplanasi penyuluhan multimedia tentang pencegahan anemia terhadap perilaku remaja putri mencegah anemia - Heru Subaris Kasjono; Mia Dwi Agustiani; Sunartono Sunartono (Health Sciences and Pharmacy Journal, 2021)
The way to cut off the chain of stunting is by inplanting clean and healthy living behaviors and consuming balanced nutrition in adolescent girls. Counseling using multimedia is more interesting than audio and visual, so it makes easier for teenagers to understand in stunting prevention.this study aims to analyze the explanation of multimedia counseling about prevention of anemia on adolescent girls behavior to prevent anemia. This study used pretest - posttest with control group design, with a quasi-experimental. The study population was 259, the samples were 90 respondents who were devided equally, they were 45 respondents to experiment groups and control groups selected by simple random sampling. Experiment groups used multimedia, while control groups used lecture and PPT. Respondents were given multimedia counseling about anemia prevention, behavioral questionnaire. Capillary blood test was conducted using Quik-Check, and the respondents were followed up every week and evaluated for 5 weeks. The results were tested using T-Test and linear regression. The results of this study obtained multimedia counseling had an effect on behavior (t = -2.22; CI = 95%; -4.628- -0.260; p value = 0.029). There was a multimedia explanation of the behavior of adolescent girls in preventing anemia.